The Objects and Ikea’s Environmental Imaginary - Barbalace, Francesco (Italian Sociological Review, 2024)
The purpose of this article is to illustrate the sociological implications of everyday objects, highlighting the social connections they establish within the collective imaginary. Through theoretical research on the role of objects, it examines the social imaginaries created and institutionalized by specific objects and the community of consumers involved. Ikea, the narratives crafted by corporate marketing, and its products are the specific focus of this study. In the conclusions, the meanings associated with the environmentalism imaginary (of which Ikea is an example) are explored to understand current social dynamics.